(3OjhGf GdUHGHIs - (3GHf CHj MLdI , CMeO Hf jMji Hf CHj HcQ GdJdeSGfj, TgGH GdOjf CHh GdYHGS,J (B776 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd ddYGTbjf HCMcGe GdZQGe QVG (B((3hHYO(B) (3aEf cJGHfG gPG cJGH Mhi CNHGQ ef bJd Gdghi, hSGQ Hge aj GdMH cd ePgH s
(3BNQgG (B:s
(3hbO eGJ bdHj Chd GdMH hCfbVi adh eJ CeS GdMH bO eGJ BNQg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B268s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B139 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B796s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdeJMa GdYQGbj HHZOGO (B(1241) s
Keywords: (3GdCOHs